Peranan Kegiatan Ekstrakurikuler Pramuka Untuk Memperkuat Pendidikan Karakter Peserta Didik di Sekolah Menengah Atas - Triandewi, Ni Komang Cahyani; Yudana, I Made; Sidaryanti , Ni Nyoman Asri (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
Character education is a primary focus of the national education system, as an effort to shape students who excel not only academically but also possess personality, morals, and social attitudes consistent with the values ​​of Pancasila. One strategy considered effective in strengthening character education is through extracurricular activities, particularly scouting activities, which emphasize hands-on, experiential learning. This study aims to examine the role of scouting extracurricular activities in strengthening character education for students at SMA Negeri 1 Mengwi. This study used a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation. Research informants included the principal, vice principal for student affairs, scout leaders, and students participating in scouting extracurricular activities. The results show that scouting extracurricular activities play an important role in strengthening students' character of discipline, responsibility, and independence through structured, sustainable, and hands-on activities. Although several obstacles were encountered in their implementation, such as limited time and physical readiness of students, these obstacles can be overcome through ongoing coaching and mentoring by scout leaders. Thus, extracurricular scouting activities significantly contribute to strengthening character education in schools. Keywords: Scout Extracurricular, Character Education, Discipline, Responsibility, Independence